Budaya dan Islam: Menelisik Pesan Dakwah dalam Tradisi Kaboro Weki pada Pernikahan Adat Masyarakat Parado, Kabupaten Bima - Salmiati Salmiati; Ardi Marinda (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2025)
This study examines the practice of Kaboro Weki in wedding ceremonies in Parado District, Bima Regency, with a focus on the da’wah messages embedded in the tradition. The research employs a descriptive qualitative method using a sociological approach and a cultural da’wah perspective. Data were collected through interviews, observations, and documentation involving community leaders, religious figures, and local residents. The findings indicate that the Kaboro Weki procession in wedding ceremonies consists of several stages: (1) kahaba angi, namely conveying information and messages to the extended family; (2) doho kaboro, a deliberative gathering to discuss shortcomings and preparations for the wedding; (3) kahaba ra hukum la’o sara, the delivery of marriage information to village authorities and the wider community; (4) doho sara, a deliberative meeting involving the government and the community; and (5) the implementation of the agreed wedding activities. Furthermore, the da’wah messages contained in the Kaboro Weki tradition include values of conveying good news, mutual respect, honesty, commitment, brotherhood, charity, mutual assistance, and deliberation. These values demonstrate that Kaboro Weki functions not only as a cultural tradition but also as an effective medium of cultural da’wah in strengthening social harmony and religious values within the community.